Experiences of women raising children with congenital Zika syndrome along a trajectory of prevention, care and support in Brazil. Issue 12 (2nd December 2022) - Morris, Maximilian; Brito, Ana; Malta, Monica; Jacques, Iracema; Rocha, Grizielle; Novaes, Rayanne; Mantsios, Andrea; Kerrigan, Deanna
ABSTRACT: Social science research investigating the social dynamics of Zika and congenital Zika syndrome (CZS) is essential to inform future services related to Zika and other infectious diseases. We sought to understand lived experiences with Zika during pregnancy, birth, and post-partum by conducting in-depth interviews with a sample of 31 women infected with Zika during the 2015–16 outbreak who had a child with CZS in Pernambuco, Brazil. Transcripts were coded using thematic content analysis. Many women experienced shock when their children were born with CZS given the lack of information they were provided during the antenatal period. Stigma from loved ones and community members was a salient theme as were financial difficulties arising from women having to stop working to care for their child. While women experienced significant challenges caring for a child with CZS, they also exhibited resiliency in their ability to move from shock and sorrow to focusing on the needs of their child. While support services were generally available, they were often located at a significant distance. Results underscore the need for interventions to improve patient-provider communication, address socio-structural stressors, and support individual and collective resilience in women and families affected by Zika in lower resource settings.